Detection of copy number variations in epilepsy using exome data. Issue 3 (25th January 2018) - Tsuchida, N.; Nakashima, M.; Kato, M.; Heyman, E.; Inui, T.; Haginoya, K.; Watanabe, S.; Chiyonobu, T.; Morimoto, M.; Ohta, M.; Kumakura, A.; Kubota, M.; et al.
Abstract : Epilepsies are common neurological disorders and genetic factors contribute to their pathogenesis. Copy number variations (CNVs) are increasingly recognized as an important etiology of many human diseases including epilepsy. Whole‐exome sequencing (WES) is becoming a standard tool for detecting pathogenic mutations and has recently been applied to detecting CNVs. Here, we analyzed 294 families with epilepsy using WES, and focused on 168 families with no causative single nucleotide variants in known epilepsy‐associated genes to further validate CNVs using 2 different CNV detection tools using WES data. We confirmed 18 pathogenic CNVs, and 2 deletions and 2 duplications at chr15q11.2 of clinically unknown significance. Of note, we were able to identify small CNVs less than 10 kb in size, which might be difficult to detect by conventional microarray. We revealed 2 cases with pathogenic CNVs that one of the 2 CNV detection tools failed to find, suggesting that using different CNV tools is recommended to increase diagnostic yield. Considering a relatively high discovery rate of CNVs (18 out of 168 families, 10.7%) and successful detection of CNV with <10 kb in size, CNV detection by WES may be able to surrogate, or at least complement, conventional microarray analysis. Abstract : Whole‐exome sequencing (WES) was performed in a total of 294 families with epilepsy. Then, WES‐based copy number variation (CNV) detection in 168 families were conducted after excluding 126 families with causative single nucleotide variants, and 18 families with pathogenic CNVs were identified. CNVs were detected in 2 ways: (1) 2‐step detection: eXome Hidden Markov Model (XHMM) and subsequent Nord's method (left in a dotted box) and (2) Nord's method targeting 303 epilepsy genes (right in a dotted box). Seventeen and one pathogenic CNVs were detected by methods (1) and (2), respectively.